2022
DOI: 10.1093/jicj/mqac002
|View full text |Cite
|
Sign up to set email alerts
|

Shredded

Abstract: From 2012 to 2016, the Colombian Government and the FARC-EP guerilla group sought to end the region’s longest non-international armed conflict. Under the auspices of the international community, this process drew from a complex series of practices and knowledge often known as ‘transitional justice’. Indeed, international expertise — in law and other fields — was also actively mobilized by both parties, as well as civil society and the anti-peace opposition, to contest the meaning of these terms. On paper, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Ramírez‐Gutiérrez and Quiroga‐Villamarín conclude that JEP, like other judicial institutions, plays a crucial role in creating narratives about the conflict and the possibilities of reconciliation. Even in the so‐called post‐conflict context, the warring parties will attempt to use [mechanisms of mass and new media] to consecrate their vision of truth (Ramírez‐Gutiérrez & Quiroga‐Villamarín, 2022). Piccone also found that political disputes have hindered JEPs progress as real‐time, public perception of the trials increased attention and scrutiny on political officials, leading to disputes and decreased judicial effectiveness (Piccone, 2019).…”
Section: Framework Application In Post‐conflict Colombiamentioning
confidence: 99%
“…Ramírez‐Gutiérrez and Quiroga‐Villamarín conclude that JEP, like other judicial institutions, plays a crucial role in creating narratives about the conflict and the possibilities of reconciliation. Even in the so‐called post‐conflict context, the warring parties will attempt to use [mechanisms of mass and new media] to consecrate their vision of truth (Ramírez‐Gutiérrez & Quiroga‐Villamarín, 2022). Piccone also found that political disputes have hindered JEPs progress as real‐time, public perception of the trials increased attention and scrutiny on political officials, leading to disputes and decreased judicial effectiveness (Piccone, 2019).…”
Section: Framework Application In Post‐conflict Colombiamentioning
confidence: 99%
“…105 At this point, Hoyos and his allies realised that they could use the categories of international humanitarian law for their own far-right political agenda, which were quite different from the seemingly progressive and liberal aims of the 'humanitarian consciousness'. 106 If the new FARC peace process was one which was not only thoroughly 'juridified' 107 but also 'judicialised,' 108 then the far right stood much to gain if it managed to mobilise these concepts for its illiberal purposes. 109 It is important to note that 'impunity' is a legal category, and not merely of a moral nature.…”
Section: 'For Freedom and Against The Atrocities Of Terrorism': Hoyos...mentioning
confidence: 99%
“…114 As I have explained in more detail elsewhere, in the 2012 Havana processin contrast to the 2005 paramilitary demobilisation process -'compliance with international standards [on the rights of victims] took centre stage'. 115 For this reason, the Havana negotiators (with much advice from international experts) created an 'integrated system of Truth, Justice, Reparation, and Non-Repetition', of which the JEP was the crown jewel. This Special Jurisdiction was tasked with the implementation of a regime of alternative, non-prison-based punishments.…”
Section: 'For Freedom and Against The Atrocities Of Terrorism': Hoyos...mentioning
confidence: 99%